Islāmically modified cognitive behavioural therapy - Qasqas, Mahdi (Routledge, 2025)
"This book outlines the methods and practice of Islāmically Modified Cognitive Behavioural Therapy (IMCBT), a modified version of CBT adapted to the Muslim client's preferences, culture, and religion. The book begins by establishing IMCBT's fidelity to the core competencies and evidence-based practices of CBT while also introducing new unique features and interventions related to Muslim clients. It uses real-life cases to offer practical strategies for overcoming stigma, forming the therapeutic alliance, structuring the session, and utilizing the client's faith for coping and problem-solving. Chapters comprehensively provide CBT skills competencies with Islāmic modifications for a range of topics including case conceptualization, reframing, cognitive restructuring, and advanced coping strategies for addressing interpersonal conflicts and enhancing therapeutic outcomes. The book also offers both proscriptive and prescriptive ethical guidance by showcasing instances where clients experienced negative outcomes with other practitioners to emphasize the dangers of not properly preparing for and understanding how to work with Muslims who prioritize their faith. This text will appeal to practitioners, educators, and students who are seeking deeper ways of adapting their practice, teaching, or learning to the Muslim client's needs while also maintaining fidelity to the core features of CBT"-- Provided by publisher.
Keywords: Psychotherapy -- Religious aspects -- Islam.; Cognitive therapy.; Muslims -- Mental health.; elektronické knihy; electronic books